Immunosuppression and Outcomes in Patients with Cutaneous Squamous Cell Carcinoma of the Head and Neck - Doriana Iancu; Ana Fulga; Doina Vesa; Iuliu Fulga; Dana Tutunaru; Andrei Zenovia; Alin Ionut Piraianu; Elena Stamate; Corina Sterian; Florentin Dimofte; Mihail Alexandru Badea; Alin Laurentiu Tatu (Clinics and Practice)
Cutaneous squamous scell carcinoma (cSCC) is a frequent non-melanoma skin cancer that originates from keratinocytes with increased prevalence. cSCC can be either in situ, as in Bowen’s disease, or extended. Advanced age, accumulated sun exposure, light pigmentation, and prior skin cancer diagnosis are all significant risk factors for cSCC. Although most cSCCs can be treated surgically, some recur and metastasize, resulting in death. The role of immune status is not yet determined in the prognosis of these patients. Objective. Immunosuppressed patients are more likely to develop cSCC, which is often characterized by more aggressive, multifocal lesions. This study aimed to determine the risks of mortality in patients with cSCC and immunosuppression versus non immunosuppression and to compare variations in overall survival based on different clinical features. Method. We evaluated clinical cases of patients at “Sfantul Apostol Andrei” Emergency Hospital of Galati, Romania, from 1 March 2018 to 1 April 2024. Subjects in the trial had to be at least 18 years old and have a pathologically confirmed diagnosis of cutaneous head and neck squamous cell carcinoma (cHNSCC). We divided the patients into two different categories based on whether they had immunosuppression. Results. In this cohort of 68 subjects with cSCC, patients with immunosuppression had significantly lower overall survival, as well as lower three- and five-year survival rates compared with those without immunosuppression, even after adjustment for age, sex, stage, and previous surgical treatment. The median survival time for immunosuppressed individuals ranged from 11 to 21 months, varying based on their particular characteristics, and most critically, on the presence of other malignancies, while that of immunocompetent patients ranged from 18 to 51 months. In addition, immune-deficient patients with early-stage disease had a 21-month median survival rate that changed to11 months for advanced-stage cases. In a similar manner, immunocompetent patients with early-stage cancer had a significantly better median survival than those withadvancedstages,43 versus 18months. Our results indicate that immunosuppression is a distinct risk factors associated with a less favorable outcome in patients with cHNSCC.